GRAMMATICAL ERROR ANALYSIS ON STUDENTS`WRITING OF APPLICATION LETTER AT 12TH GRADE OF VOCATIONAL HIGH SCHOOL - Irma Wahyuni; Putri Dewi Melia (JELLi Journal, 2020)
This research is qualitative research. The objective of the research is to determine the students' ability in writing application letters and analyzing grammatical error in writing application letters. The subject of the research is twelfth grade students of SMK Pertiwi, located in Cibungbulang-Bogor. The purposive sampling is sample to determine the class that would treatment. Purposive sampling is sampling based on certain considerations such as population characteristics or previously known characteristics. The sample of the research is the twelfth-grade students consisting of 10 students from two classes. The data collecting technique of the research used questionnaire and writing test. The result of the research from the data, the writer described the percentage based on the type of error. First, omission, there were 10 errors of omission that found on the students` writing application letter. The percentage of omission error was 77%. Second, There were 6 errors of misformation. The percentage of misformation error was 46%. Third, addition. There were 4 errors of addition. The percentage of addition error was 31%.. Last, misordering. There were 2 errors of misordering. The percentage of misordering error was 15%. Based on the results that the students still have so many lack of vocabulary, lack of understanding on grammar, they though English was very difficult because it was a foreign language. Students also realized that they still had luck of grammar mastery, and practice